Allometry and sexual dimorphism of the Neotropical freshwater anomuran Aegla marginata Bond-Buckup & Buckup, 1994 (Crustacea, Anomura, Aeglidae) - Silva, Alexandre Ribeiro Da (2017)
Abstract This study analyzes ontogenetic allometry in Aegla marginata Bond-Buckup & Buckup, 1994, a freshwater crustacean, in order to evaluate the growth pattern and the presence of sexual dimorphism, using a multivariate approach. The specimens were sampled from streams in Intervales State Park, São Paulo State, Brazil. For each specimen, we measured the following structures: carapace length and width, chelae height and length, and abdomen length. Allometry was evaluated using Jolicoeur’s multivariate allometric coefficient. Our results showed that for females, ABL (abdomen length) and LCH (left chelae heigh) presented positive allometry; LCL (left chelae length) and RCH (right chelae heigh) isometry; and CL (carapace length), CW (carapace width), and RCL (right chelae length) negative allometry. For males, RCH, LCH, and LCL presented positive allometry; RCL (right chelae length) isometry; and CL, CW, and ABL negative allometry. In addition, sexual dimorphism was amplified with body size.